Influence of material composition on flame spread behavior over combustible solid of paper/bagasse - Ramli, Afifah; Razali, Mohd Azahari; Madon, Rais Hanizam; Khalid, Amir; Mohmad Ja’at, Md Norrizam; Manshoor, Bukhari (Penerbit UTHM, 2018)
Fire Safety Engineering is an application of science to improve the safety from the destructive effect of the fire. Paper is one of sources that easily catch fire, however, research on flame spread towards paper is still not enough to describe about the phenomenon. Inspiration from this, the behavior of downward flame spread over paper/bagasse is experimentally investigated. Composition of 0%, 30%, 50%, 70% and 100% bagasse is chosen for this research. Flame spread behavior for each composition is analyzed from the observation. Results show for each composition, the flame spreads with “U” shape at the beginning of combustion until the whole specimen. The result shows that the flame spread rate decreases as bagasse composition increases. The highest flame spread is 0.813 mm/s for pure paper and the lowest one is 0.481 mm/s for pure bagasse. Not only that, it also shows the flame spread rate decreases as the density increases. It is clarified that density for bagasse is higher than paper. Result infers that the flame spread shape and rate are not only influenced by the bagasse composition but also by the density